PENGARUH PEMBERIAN TOPIKAL EKSTRAK ETANOL DAUN PECUT KUDA (Stachytarpheta jamaicensis (L.) Vahl) TERHADAP PENYEMBUHAN LUKA BAKAR DERAJAT II PADA PUNGGUNG KELINCI (Oryctolagus cuniculus) - Muhammad Anggriawan; Yuliet Yuliet; Khildah Khaerati (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Pecut kuda (Stachytarpheta jamaicensis (L.) Vahl) is one of plant that has the potentials to heal various diseases, one of them as an alternative in the cure of burns. Pecut kuda leaf has been used hereditary by some people at Layana Wintu, Mantikulore subdistrict, Donggala regency for cure of burns. This research is conducted to find out the effect of topical administration of ethanol extract of pecut kuda leaf towards healing burns second degree on the rabbit’s back (Oryctolagus cuniculus) by using many extract concentration variation which are 1%, 3% and 5% with gel basic as the carrier. Testing was conducted on 5 rabbits, each rabbit was induced on his back by 5 burns for five treatments with burns diameter is 2 cm . Burns that has been induced was given each treatments which are negative control (gel basic without extract), ethanol extract of pecut kuda leaf in basic gel with each concentration 1%, 3% and 5%. Positive control used bioplacenton gel. Later, the burns diameter was measured on certain day during 28 days. Data that are achieved was statistically analyzed with one way anova method and is continued by testing post hoc duncan with 95% confidance level. The reasult of this research shows every extract ethanol concentration variation of pecut kuda leaf have activity to heal burns. Extract ethanol concentration of pecut kuda leaf which is efective in healing burns is 3% concentration.Keywords: Gel, (Stachytarpheta jamaicensis (L.) Vahl), Burns, Oryctolagus cuniculus